Survival of Microorganisms on Inanimate Surfaces - Kramer, Axel (Use of Biocidal Surfaces for Reduction of Healthcare Acquired Infections, 2014)
In healthcare settings microbial contaminated surfaces play an important role in indirect transmission of infection. Especially surfaces close to the patients’ environment may be touched at high frequencies, allowing transmission from animated sources to others via contaminated inanimate surfaces. Therefore, the knowledge on the survival of bacteria, fungi, viruses and protozoa on surfaces, and hence, in a broader sense, in the human environment, is important for implementing tactics for prevention of Healthcare-acquired Infections (HAI). This chapter will elaborate the role of surfaces in the transmission of pathogens. Particular emphasis is laid on the current knowledge of the survival time and conditions favouring survival of the pathogens. Finally, mechanisms of transmission from inanimate surfaces to patients are highlighted. Within the multi-barrier strategy of the prevention of HAI, environmental disinfection policies should be based on risk assessments for surfaces with different risks for cross contamination such as high- and low-touched surfaces with appropriate standards for adequate disinfection measures under consideration of the persistence and infectious dose of the pathogens. As a result, surface disinfection is indicated in the following situations: Frequently touched surfaces adjacent to patients. Surfaces with assumed or visible contamination. Terminal disinfection in rooms or areas where infected or colonized patients with easily transferable nosocomial pathogens are cared for, and in outbreak situations. Furthermore, the knowledge of the persistence of pathogens will also support ensuring the biosafety in microbiological and biomedical laboratories, food-handling settings, and for hygienic behaviour in the everyday life to prevent transmission of infectious diseases.